Upper limb motor recovery in chronic stroke—longitudinal aggregate analysis from control group outcomes - Scalzo, Fabien; Coker, Robert A.; Souders, Lauren; Petrossian, Leo; Bhugra, Kern; Sheehan, Lauren; Leuthardt, Eric C.; Carter, Alexander R. (Frontiers in Rehabilitation Sciences, 2025)
IntroductionThis study examines the effects of regular physical activity on upper extremity motor recovery during the late subacute and chronic phases of stroke.MethodsData were aggregated from 20 studies comprising 368 participants in control groups receiving usual care or general rehabilitation without specialized interventions. To isolate the impact of non-specific physical activity, studies involving robotics or task-specific therapies were excluded.ResultsThe primary outcome was the change in Fugl-Meyer Assessment of Upper Extremity (FMA-UE) motor scale. The pooled effect size for FMA-UE change was small and non-significant (Cohen's d = 0.11, 95% CI: −0.05 to 0.26, p > 0.05), indicating that general physical activity alone may result in limited improvements in upper extremity function in chronic stroke. Heterogeneity across studies was low, and no evidence of publication bias was found.DiscussionThese findings provide a quantitative benchmark for expected gains from general activity and offer a reference for interpreting outcomes in future stroke rehabilitation trials lacking control groups.